Manajemen Kurikulum Pendidikan Islam Berbasis Deep Learning: Model Pengembangan Keterampilan Berpikir Kritis Mahasiswa - Juni Erpida Nasution; Lidya Larassati; Arfi Sholahuddin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Islamic education in the digital era faces significant challenges in improving the quality of learning and developing students' critical thinking skills. One promising solution is the implementation of deep learning-based Islamic education, which can facilitate the teaching of religious material more effectively and easily accessible via the internet. Deep learning has the potential to strengthen students' critical thinking skills and understanding of Islamic values ​​in a more interactive and personalized manner. This study used a literature review method to analyze various relevant literature sources. The results indicate that deep learning can increase student engagement, enable personalized learning, and provide real-time evaluation of learning progress. However, the implementation of this technology also faces challenges, particularly related to the availability and quality of relevant data. Therefore, efforts are needed to improve data quality and develop learning models tailored to student needs to achieve optimal results in technology-based Islamic education.